Validation and application of a total dietary fiber determination method to meat products. (September 2019) - Bajcic, A; Petronijevic, R B; Vranic, D; Trbovic, D; Betic, N; Nikolic, A; Milojevic, L
Abstract: This paper presents a modification of the reference method for the determination of dietary fiber in food, its validation using two quality control materials and application to meat products. Dietary fiber is a very important food ingredient with multiple positive effects in human nutrition. In recent decades, efforts have been made to enrich with fiber some foods that do not naturally contain fiber to a significant extent, such as meat products. Fiber content must be declared in accordance with legal regulations, and it is necessary to have reliable methods for determining their amount in food. The results obtained show the described modified and optimized method can be applied to meat products, with significant savings in the preparation time and consumption of reagents.